2020
DOI: 10.1038/s41467-019-14116-y
|View full text |Cite
|
Sign up to set email alerts
|

Control of locomotor speed, arousal, and hippocampal theta rhythms by the nucleus incertus

Abstract: Navigation requires not only the execution of locomotor programs but also high arousal and real-time retrieval of spatial memory that is often associated with hippocampal theta oscillations. However, the neural circuits for coordinately controlling these important processes remain to be fully dissected. Here we show that the activity of the neuromedin B (NMB) neurons in the nucleus incertus (NI) is tightly correlated with mouse locomotor speed, arousal level, and hippocampal theta power. These processes are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 69 publications
4
89
1
1
Order By: Relevance
“…The present results help to clarify the neurotransmitter identity of neurons in this region of the pontine tegmentum as a basis for future functional studies. Lu et al reported that about 50% of NMB expressing neurons in the NI also express Rln3, although only a single anatomical level was described (Lu et al, 2020). Here, in the region usually defined as the NI, we observe a higher degree of co-expression of NMB and Rln3 mRNA, with a minor population of neurons expressing NMB alone.…”
Section: Discussionmentioning
confidence: 38%
See 4 more Smart Citations
“…The present results help to clarify the neurotransmitter identity of neurons in this region of the pontine tegmentum as a basis for future functional studies. Lu et al reported that about 50% of NMB expressing neurons in the NI also express Rln3, although only a single anatomical level was described (Lu et al, 2020). Here, in the region usually defined as the NI, we observe a higher degree of co-expression of NMB and Rln3 mRNA, with a minor population of neurons expressing NMB alone.…”
Section: Discussionmentioning
confidence: 38%
“…Expression of Rln3 has been used as a defining marker of the NI in rodents and primates (Burazin et al, 2002;Ma et al, 2007;Ma et al, 2009a), although the area encompassing the anatomical NI contains a mixture of Rln3 expressing and non-expressing neurons (Ma et al, 2007). Recently, expression of Cre-recombinase targeted to the Nmb gene has also been used for functional studies of the NI (Lu et al, 2020). The present results help to clarify the neurotransmitter identity of neurons in this region of the pontine tegmentum as a basis for future functional studies.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations